Improving Student Learning Outcomes through Problem Based Learning Model in Islamic History Learning at MIS Nurul Iman Pilomonu - Sudi, Kamilia; Adju, Marlina (MANDAILING GLOBAL EDUKASIA, 2025)
The low learning outcomes of students on the Sunan Gunung Jati material have been proven by the results of the pre-test on the Sunan Gunung Jati material from 14 students of class VI MIS Nurul Iman Pilomonu. Based on the results of the student pre-test, the classical completion value was obtained by 5 students or 35.7% who managed to achieve the KKM score. And students who have not achieved the classical completion target are 9 students or 64.2%. The KKM value is 75. Seeing this statement, it can be said that the problem above, the author is interested in researching and testing the extent to which the learning outcomes of SKI (History of Islamic Culture) on the Sunan Gunung Jati material through the problem based learning model. This research method uses the classroom action research method (Classroom Action Research). This research took place at MIS Nurul Iman Pilomonu. The subjects of this study were class VI students of MIS Nurul Iman Pilomonu in the 2023/2024 academic year. The number of class VI is 14 students. The data collection method in this study is the observation method, test method, interview and documentation. In the pre-cycle, the number of students who completed learning reached 5 students. The average value only reached 62.75, which means it is still below the KKM. In the pre-cycle, an observation score of 2.14 was produced, meaning that students who were active in learning only reached around 20-30%. In cycle I, the number of students who completed learning reached 9 students, the average value reached 74.5. This means that the problem based learning model is effectively used to improve student learning outcomes in the Sunan Gunung Jati material. In student observation activities, the teacher assesses that knowledge is experienced, learned, and discovered by students, students do something to understand the subject matter (building understanding), students communicate their own thoughts, students think reflectively and students can work in groups with other friends. In cycle II, the number of students who completed learning reached 14 students, the average value reached 81.5. This means that the problem based learning model is effectively used to improve student learning outcomes in the Sunan Gunung Jati material. In cycle II, the observation score was 5.71, meaning that students who were active in learning reached around 80-10%.